The stakes in the State U a stakeholder analysis of the Socialized Tuition and Financial Assistance Program - Diaz, Rooster C.; Lauengco, Francesca M. (2013)
"The Stakes in the State U: A Stakeholder Analysis of the Socialized Tuition and Financial Assistance Program is an analysis of the perceptions of the stakeholders-students, parents and the administration-on the Socialized Tuition and Financial Assistance Program (STFAP) of the University of the Philippines. The researcher's main aim is to find out the similar and varying perceptions of the stakeholders on the program. In line with this objective, the conceptions and opinions, expectations, roles and recommendations of the stakeholders were also discerned in this study. This research endeavour also evaluated the communication materials of the program and traced the evolution of the STFAP. In order to reach these goals, the researchers used a qualitative research design to be able to explore further the field or study. Key informant interviews were made with the Pfficer-in-Charde of the STFAP Section of the Office of Scholarships and Students Services (OSSS), and with two expert professors who have done researches on the program. Focus interviews were conducted with the administration members-a college dean, a member of the faculty and an administration staff. This data gathering method was also done with students from the different STFAP brackets and with their parents. For analysis of the communication materials, evaluation was based on various credible literatures that the researchers were able to obtain. A document analysis was utilized in order to trace the changes of the STFAP. Results showed that stakeholders have different stances on the program, depending on their awareness, knowledge and benefits from the STFAP. There are also similar understandings of the technical aspects of STFAP among the stakeholders however; opinions on the program vary among them. Consequently, information dissemination materials were found to be potentially effective, but these cane be improved further, expecially when it comes to the aesthetic aspect of the materials. It has also been seen that the program has undergone a lot of changes in order to keep up with the demands of the economic aspect of the country and the needs of the students and their families. Through the information gathered from this research, the researchers posted that the end of this paper different suggestions and recommmendations to further improve the communication and understanding of STFAP among the stakeholders."